Metabolic alterations and metabolic syndrome in HIV infected patients induced by highly active antiretroviral therapy from Arzobispo Loayza National Hospital - a pilot study - Valencia Arroyo, Braulio M. (2008)
Introduction: Human immunodeficiency virus (HIV) infection is an important public health problem. Even though highly active antiretroviral therapy (HAART) has improved patient survival, there are some important secondary metabolic complications.Objectives: To describe epidemiological features, metabolic alterations, and metabolic syndrome rates in HIV-infected patients receiving HAART, as well as to determine whether there is any statistical association between such alterations and the therapy they are receiving.Material and Method: This is a pilot cross-sectional study carried out between November 2006 and June 2007 in male and female patients between 18 and 40 years of age from the Infectious Disease service of Arzobispo Loayza National Hospital, with a confirmed diagnosis of HIV infection (ELISA + Western Blot), with CD4 cell and viral load counts no more than 6 months old and who are receiving HAART during at least six months using well defined schedules. Weight, height and abdominal circumference were measured, and also fasting serum levels of total cholesterol, HDL cholesterol, LDL cholesterol, triglycerides, blood sugar and insulin were determined.Results: 36 patients entered the study. 5.6% of them had metabolic syndrome; hypertriglyceridemia and low levels of HDL cholesterol were the most frequent metabolic alterations. There was a statistically significant difference when triglycerides and blood glucose values were measured according to the HAART schedule (p= 0.0094 and P= 0.0019, respectively), and the highest values for the aforementioned parameters were found in those patients receiving scheme III (p= 0.01 and p= 0.002, respectively) including stavudine, lamivudine, and nevirapine.Conclusions: Hypertriglyceridemia and low levels of HDL cholesterol were most frequently found metabolic alterations, statistically significantly different according to different HAART schedules. It is important that the aforementioned alterations are more frequent when using nevirapine containing regimens, since this drug has been widely used as a replacement of protease inhibitors because of unfavorable side effects.